2021
DOI: 10.1183/13993003.02124-2021
|View full text |Cite
|
Sign up to set email alerts
|

Bedaquiline can act as core drug in a standardised treatment regimen for fluoroquinolone-resistant rifampicin-resistant tuberculosis

Abstract: Bedaquiline can act as core drug in a standardized treatment regimen for fluoroquinolone-resistant rifampicin-resistant tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Introducing bedaquiline [8] throughout the treatment period makes us able to cure the patient, although the duration of the therapy was extended to 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Introducing bedaquiline [8] throughout the treatment period makes us able to cure the patient, although the duration of the therapy was extended to 5 years.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 21 Recently published data from Bangladesh support the assumption that its early killing effect is too little to sufficiently protect the regimen’s core drug against the development of resistant mutants. 54 Furthermore, Chiang et al . 51 propose to consider the utilization of injectable-containing short MDR-TB regimens again.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it could be shown that the replacement of the FQ by bedaquiline using the Bangladesh regimen (including the injectable kanamycin) in case of high-level FQ resistance results in higher rates of culture conversion and relapse-free cure, thus demonstrating that bedaquiline but not linezolid can act as core drug for the treatment of patients with FQ-resistant RR-TB. 54 …”
Section: Discussionmentioning
confidence: 99%
“…DECROO et al [13] added to the body of knowledge how to manage the treatment of TB resistant to the most important first-line anti-TB drug, rifampicin, when resistance to fluoroquinolones is unknown. Given the complexity of describing details of the regimens evaluated in a short editorial, we invite the interested reader to read the manuscript.…”
Section: Tb Diagnosismentioning
confidence: 99%